Lama Waktu Tidur Dengan Kejadian Obesitas Pada Remaja (Case Control Study): Length of Sleep with the Incidence of Obesity in Adolescents (Case Control Study) - Susmiati (NERS Jurnal Keperawatan, 2017)
The study on sleep duration has long been studied on various ethnic groups in developed countries, yet only a few have been conducted in developing countries. There is no information on the association between sleep duration and obesity on adolescents of Minangkabau ethnic. Based on the aforementioned reasons, there need a research on the association between sleep duration and obesity on adolescents. The aim of this study is to investigate the relationship between sleep duration and obesity on adolescents. The study was conducted by cross-sectional method. Samples comprise 178 junior high school students (91 obese and 87 non-obese) aged between 12-15 years in two regencies in West Sumatera. Independent variable was sleep duration, and obesity was dependent variable. Sleep duration was measured using self-reported sleep duration questionnaire and obesity was measured by anthropometric measurement. Statistical analysis was performed using SPSS. Data was analysed using student t-test, chi-square, and correlation analysis with p < 0.05 being significant. There was no significant diference between sleep duration and obesity prevalence, p= 0.45. The t-test on mean sleep duration suggested that there was no significant difference between sleep duration of normal and obese respondents p= 0.34. There was an association between sleep duration and body fat percentage. Modification of sleep duration may be an alternative to reduce obesity prevalence.